Traditional and modern foods - Balogh Sándor; Snelcer Betti; Traditions, innovation, sustainability (2011) (Hódmezővásárhely) (Szegedi Tudományegyetem Mezőgazdasági Kar Szeged, 2011)
The lecture aims to present the “family tree” which shows the “phylogeny“ of foods and which demonstrates that the process of product development in food industry shows a certain, largely predictable regularity.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák